2022
DOI: 10.1002/bies.202200084
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA‐sequencing: A powerful yet still challenging technology to study cellular heterogeneity

Abstract: Almost all biomedical research to date has relied upon mean measurements from cell populations, however it is well established that what it is observed at this macroscopic level can be the result of many interactions of several different single cells. Thus, the observable macroscopic ‘average’ cannot outright be used as representative of the ‘average cell’. Rather, it is the resulting emerging behaviour of the actions and interactions of many different cells. Single‐cell RNA sequencing (scRNA‐Seq) enables the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 144 publications
0
17
0
Order By: Relevance
“…Research in many areas of biology focuses on single-cell studies, particularly single-cell RNA sequencing (scRNA-seq) mainly using microfluidic-based methods [1][2][3][4][5][6] , with the 10x Genomics Chromium instruments achieving particularly wide usage 7 . Comparative benchmarking has been reported for many of the available methods (including CEL-Seq2,…”
Section: Progress In Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in many areas of biology focuses on single-cell studies, particularly single-cell RNA sequencing (scRNA-seq) mainly using microfluidic-based methods [1][2][3][4][5][6] , with the 10x Genomics Chromium instruments achieving particularly wide usage 7 . Comparative benchmarking has been reported for many of the available methods (including CEL-Seq2,…”
Section: Progress In Sample Preparationmentioning
confidence: 99%
“…A convenient stopping point after two hours has been established by freezing at the cell lysis step, with full preservation of gene expression profiles. Overall, our results show that RevGel-seq represents an accessible and efficient instrument-free alternative, enabling flexibility in terms of experimental design and timing of sample processing, while providing broad coverage of cell types.Research in many areas of biology focuses on single-cell studies, particularly single-cell RNA sequencing (scRNA-seq) mainly using microfluidic-based methods [1][2][3][4][5][6] , with the 10x Genomics Chromium instruments achieving particularly wide usage 7 . Comparative benchmarking has been reported for many of the available methods (including CEL-Seq2,…”
mentioning
confidence: 99%
“…Nevertheless, these studies are limited by their approach of assessing cell populations instead of single cells, thus ignoring potential heterogeneity within the production platform. Moreover, single‐cell RNA‐sequencing (scRNA‐seq) would have the added benefit of identifying subpopulations of cells with distinct gene expression profiles, which might result in phenotypically beneficial traits (Ke et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, single-cell RNA-sequencing (scRNA-seq) would have the added benefit of identifying subpopulations of cells with distinct gene expression profiles, which might result in phenotypically beneficial traits (Ke et al, 2022).…”
mentioning
confidence: 99%
“…In particular the field of single-cell RNA sequencing has demonstrated that a lot of valuable information can be obtained even from minimal amounts of RNA. 16,17 Specifically, the protocols developed in this field advanced reverse transcription efficiency e.g. by utilization of optimized enzymes, adapted buffer conditions, addition of other reagents like crowding reagents, longer incubation times, and thermal cycling to unfold RNA secondary structures.…”
Section: Introductionmentioning
confidence: 99%